Pengaruh Literasi Digital terhadap Keterampilan Membaca dan Menulis Bahasa Indonesia - Handika Simamora; Joy Stevani Simangunsong; Sartika Sartika; Larista Larista; Josua panjaitan; Fitriani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The aim of this research is to study how digital literacy impacts the ability to read and write Indonesian from various literary sources. The ability to access, understand, use and create information through the use of digital technology is known as digital literacy. The ability to read and write in Indonesian is the ability to understand and create texts in that language, both online and offline. This study uses a qualitative method with a literature or literature study design. Data sources for this research come from various articles, books, journals and reports related to the research topic. Content analysis techniques were used to analyze the data. The research results show that digital literacy can increase students' motivation, interest and skills in reading and writing Indonesian texts.